Optimal obscurity in the acquisition and disclosure of information about a shock - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2012)
A principal acquires information about a shock and then discloses it to an agent. After the disclosure, the principal and agent each decide whether to take costly preparatory actions that yield benefits only when the shock strikes. The principal maximizes his expected payoff by controlling the quality of his information, and the disclosure rule. We show that even when the acquisition of perfect information is costless, the principal may optimally acquire imperfect information when his own action eliminates the agent's incentive to take action against the risk.
Keywords: C72; D82; 330; endogenous information; disclosure; signal quality; transparency; specific investment; strategic ignorance; Informationsverhalten; Asymmetrische Information; Investition; Entscheidung bei Unsicherheit; Nichtkooperatives Spiel; Prinzipal-Agent-Theorie; Theorie